Circulating fibrocytes as prognostic biomarkers of autoimmune interstitial lung disease. Issue 4 (10th November 2020) - Odackal, John; Yu, Victor; Gomez-Manjerres, Diana; Field, Joshua J.; Burdick, Marie D.; Mehrad, Borna
Background: Autoimmunity is a common cause of pulmonary fibrosis and can present either as a manifestation of an established connective tissue disease or as the recently described entity of interstitial pneumonia with autoimmune features. The rate of progression and responsiveness to immunosuppression in these illnesses are difficult to predict. Circulating fibrocytes are bone marrow-derived progenitor cells that home to injured tissues and contribute to lung fibrogenesis. We sought to test the hypothesis that the blood fibrocyte concentration predicts outcome and treatment responsiveness in autoimmune interstitial lung diseases. Methods: We compared the concentration of circulating fibrocytes in 50 subjects with autoimmune interstitial lung disease and 26 matched healthy controls and assessed the relationship between serial peripheral blood fibrocyte concentrations and clinical outcomes over a median of 6.25 years. Results: As compared to controls, subjects with autoimmune interstitial lung disease had higher circulating concentrations of total fibrocytes, the subset of activated fibrocytes, and fibrocytes with activation of PI3K/AKT/mTOR, transforming growth factor-β (TGF-β) receptor and interleukin (IL)-4/IL-13 receptor signalling pathways. Over the follow-up period, there were episodes of marked elevation in the concentration of circulating fibrocytes in subjects with autoimmune interstitial lung disease but not controls. Initiation of immunosuppressive therapy was associated with a decline in the concentration of circulating fibrocytes. For each 100 000 cells·mL −1 increase in peak concentration of circulating fibrocytes, we found a 5% increase in odds of death or lung function decline. Conclusion: In patients with autoimmune interstitial lung disease, circulating fibrocytes may represent a biomarker of outcome and treatment response. Autoimmune diseases are common causes of pulmonary fibrosis. The blood concentration of fibrocytes, cells involved in formation of scar tissue, predicts outcomes and response to immunosuppression in these patients. https://bit.ly/35bel62